The Existence of Madrasah Ibtidaiyah Based on Pesantren: Challenges and Opportunities in The Digital Era - Arif, Muhamad; Kartiko, Ari; Rusydi, Ibnu; Zamroni, M. Afif; Hasan, Moch. Sya’roni (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
This paper explains the process of existence of Islamic boarding school-based Madrasah Ibtidaiyah in the digital era, as Islamic boarding schools are educational institutions with quite impressive historical conditions because Islamic boarding schools can adapt to developments over time and have been proven to be academic institutions that are acceptable across society. This research uses a qualitative case study approach, interview techniques, observation, and documentation to collect data so that data analysis can be carried out. Researchers use Yin data analysis with four patterns, including pattern matching. Second, build clarity/explanation. Third, time series analysis. Fourth is repeated observation and data wetness testing through data triangulation, including methods, sources, and theory. The results of the research show that there are several efforts made by the Ibtidaiyah madrasah based on the Miftahun Ulum Kesamben Wetan Driyorejo Islamic boarding school, namely by strengthening synergy between all parties in the madrasah and outside the madrasah, as well as strengthening several conditions, including First, increasing teacher professionalism. The second is carrying out curriculum development. Third, strengthening student character as stated in the madrasa mission, and fourth, promoting literacy programs to answer challenges in the digital era.